PENGEMBANGAN MEDIA POWTOON TERHADAP KEMATANGAN KARIER SISWA KELAS X - Rahman, Isfira Reina; Mustika, Ika; Rismawati Siddik, Riesa (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2023)
This study has the aim of developing a powtoon media on student career maturity. In this study using the Research and Development (R&D) method using a model from Brog and Gall. The subjects in this study were students of class X. The results of the study were 1. Product development stage a) Phase I Preliminary study. b) Phase II includes product design, product validation, product revision, product testing. 2. The eligibility of material experts, media experts, and practitioners gets a score in the "Very Eligible" category. 3. Responses from students in the limited and broad trials got scores in the "Very Eligible" category. 4. Product feasibility from material experts, media experts, practitioners and students that powtoon media is very feasible and can be used. It can be concluded that the powtoon media on the career maturity of class X students is very feasible and can be used.